The Impacts of Firm Characteristics and Corporate Governance on Corporate Cash Holdings: An Empirical Investigation of US Companies - Li, Jiarun (2016)
This dissertation examines the impact of firm effects and corporate governance characteristics to cash holdings based the sample of US public traded firms from the period of 2004 to 2015. The Pooled OLS model, fixed effect model and SGMM model applied in this study. The final results is mostly consistent with previous study, which shows that the firm with larger size, higher amount of non-cash liquid asset and has poison pill strategy tends to holds lower amount of excess cash. Moreover, the leverage, research and development, cash flow to asset and board size are positively related to corporate cash holdings. The impacts of determinant on cash holding also examined across different industries, and the result indicate that firm size and growth opportunities have significant impacts on corporate cash holdings in most industries. Finally, the robustness check is applied to ensure the empirical result is validity.